2019
DOI: 10.24251/hicss.2019.169
|View full text |Cite
|
Sign up to set email alerts
|

Is It Human? The Role of Anthropomorphism as a Driver for the Successful Acceptance of Digital Voice Assistants

Abstract: The market of digital voice has grown significantly over the recent years. Big players like Amazon, Google, Apple, Microsoft and Samsung are focusing on the development and expansion of their assistants. Especially smart speakers are on the rise but also in smartphone integrated voice applications are getting more popular. The main characteristics of this new technology are both elements of human-computerinteraction and especially the attribution of human characteristics. Although there is an increase of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 52 publications
(85 reference statements)
1
32
1
Order By: Relevance
“…In the AIET context, the phenomenon of attributing humanlike traits to these technologies is called anthropomorphism [9,19]. Recently, anthropomorphism has been identified as an important factor influencing the perception, adoption, and continued use of AIET [12,15,16,21]. For instance, Waytz et al [21] found that anthropomorphism promoted trust in autonomous vehicles.…”
Section: Anthropomorphismmentioning
confidence: 99%
See 2 more Smart Citations
“…In the AIET context, the phenomenon of attributing humanlike traits to these technologies is called anthropomorphism [9,19]. Recently, anthropomorphism has been identified as an important factor influencing the perception, adoption, and continued use of AIET [12,15,16,21]. For instance, Waytz et al [21] found that anthropomorphism promoted trust in autonomous vehicles.…”
Section: Anthropomorphismmentioning
confidence: 99%
“…Moussawi et al [12] showed that anthropomorphism enhanced individuals' perceived enjoyment when they interacted with smart speakers, which led to an increase in adoption intention. Likewise, Wagner et al [16] reported that anthropomorphism increased smart speakers' likeability, thereby promoting the intention to adopt them.…”
Section: Anthropomorphismmentioning
confidence: 99%
See 1 more Smart Citation
“…Qiu and Benbasat [34] studied the effects of anthropomorphic embodiments in the interfaces of product recommendation agents and found that it can increase the user's perceived enjoyment and trust in the recommendation agent. A study on anthropomorphism in digital voice assistants found that a more human-like interaction between the voice assistant and the user positively influenced the likeability of the digital voice assistant, which in turn also influenced the user's intention to use the assistant again [35]. Based on the above research, practitioners can, therefore, influence the affective responses of users through implementing virtual characters, or other anthropomorphic means/techniques or tools in their interfaces.…”
Section: Resultsmentioning
confidence: 94%
“…Practitioners may also implement affective computing techniques, as there is also evidence to support their influence on the affective responses of users [31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%